Measurement verification data for AutoMorph vs. hand measurements - Hsiang, Allison Y.; Nelson, Kaylea; Elder, Leanne E.; Sibert, Elizabeth C.; Kahanamoku, Sara S.; Burke, Janet E.; Kelly, Abigail; Liu, Yusu; Hull, Pincelli M. (Zenodo, 2017)
These data include comparisons between 2D and 3D measurementsautomatically extracted by the AutoMorph software (https://github.com/HullLab/AutoMorph) and those collected manually( i.e ., using calipers, ImageJ, or VGSStudio Max for the 2D measurements, or using CT scans for the 3D measurements). These measurements are intended to demonstrate the breadth of AutoMorph's applicability, andhelp users determine whether the accuracy of AutoMorph is suitable for their needs. 2D measurements (specifically major and minor axis length and/or squared area) have been collected and presented here for fossil patellogastropods (limpets), extant bivalves, and ichthyoliths ( i.e. , fish teeth). 3D volume and surface area data have been collected for a sample of planktonic foraminifera. More information about how these data were collected, and discussion about the measurement comparisons, can be found in the manuscript describing AutoMorph (Hsiang et al. 2018). References Hsiang AY, Nelson K, Elder LE, Sibert EC, Kahanamoku SS, Burke JE, Kelly A, Liu Y, and Hull PM (2018) AutoMorph : Accelerating morphometrics with automated 2D and 3D image processing and shape extraction. Methods in Ecology and Evolution. 9(3):605-612 ( https://doi.org/10.1111/2041-210X.12915). This work was funded by the American Chemical Society PRF Grant #55837-DNI8 and by support from Yale University.